Blood Flow Restriction Exercise: Considerations of Methodology, Application, and Safety - Patterson, Stephen D.; Hughes, Luke; Warmington, Stuart; Burr, Jamie; Scott, Brendan R.; Owens, Johnny; Abe, Takashi; Nielsen, Jakob L.; Libardi, Cleiton Augusto; Laurentino, Gilberto; Neto, Gabriel Rodrigues; Brandner, Christopher; et al. (Frontiers in Physiology, 2019)
The current manuscript sets out a position stand for blood flow restriction exercise, focusing on the methodology, application and safety of this mode of training. With the emergence of this technique and the wide variety of applications within the literature, the aim of this position stand is to set out a current research informed guide to blood flow restriction training to practitioners. This covers the use of blood flow restriction to enhance muscular strength and hypertrophy via training with resistance and aerobic exercise and preventing muscle atrophy using the technique passively. The authorship team for this article was selected from the researchers focused in blood flow restriction training research with expertise in exercise science, strength and conditioning and sports medicine.